Anti- inflammatory effect of boric acid on cytokines in ovariectomy-induced rats - Tekeli, Hakan; Ekren Asıcı, Gamze Sevri; Bildik, Aysegul (Cellular and Molecular Biology, 2022)
The increase in the rate of inflammation in the post-menopause period also leads to a significant increase in the use of anti-inflammatory agents. This study aimed to investigate the effect of BA supplementation on pro-and anti-inflammatory cytokines in ovariectomy (OVX) induced rats. A total of 48 nonpregnant female Wistar albino rats (80-100 g) were used in the experiment. Forty-eight rats were divided into six equal groups (n=8): Control, OVX, OVX+5 mg/kg BA (OVX+BA5), OVX+10 mg/kg BA (OVX+BA10), 5 mg/kg BA (BA5), 10 mg/kg BA (BA10). Serum TNF-α cytokine levels of rats in the OVX group were higher than in control rats (P<0.05). TNF-α levels were significantly reduced in the OVX-induced rats with 5 mg/kg BA and 10 mg/kg BA supplementation (P<0.05). While serum IL-1α and IL-6 levels were not different between OVX and control rats, serum IL-3 levels were low (P<0.05) and not affected by 5 mg/kg and 10 mg/kg BA supplementation. Serum IL-11 levels increased significantly in the OVX rats with 5 mg/kg and 10 mg/kg BA supplementation (P<0.05). As far as we know, certain doses (5 and 10 mg/kg) of BA are the first study on the prevention of increased inflammation in rats induced by OVX. Results suggest that the supplementation of BA regulates the inflammatory changes associated with OVX and thus has beneficial for menopause management.